2022
DOI: 10.1007/s00018-022-04242-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of epithelial taste bud organoid to promote functional recapitulation of taste reactivity

Abstract: Taste stem/progenitor cells from posterior mouse tongues have been used to generate taste bud organoids. However, the inaccessible location of taste receptor cells is observed in conventional organoids. In this study, we established a suspension-culture method to fine-tune taste bud organoids by apicobasal polarity alteration to form the accessible localization of taste receptor cells. Compared to conventional Matrigel-embedded organoids, suspension-cultured organoids showed comparable differentiation and rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(62 reference statements)
2
5
0
Order By: Relevance
“…Organoid formation is a characteristic of stem/progenitor cells, and differentiated cells cannot form organoids 37 , 38 . To confirm that the differentiated cells acquired stemness by undergoing dedifferentiation, we performed a taste bud organoid formation assay as described in our previous study 39 . Dedifferentiation has been observed in various tissues during regeneration; however, subtle differences in the mechanism of dedifferentiation are observed between the taste bud and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Organoid formation is a characteristic of stem/progenitor cells, and differentiated cells cannot form organoids 37 , 38 . To confirm that the differentiated cells acquired stemness by undergoing dedifferentiation, we performed a taste bud organoid formation assay as described in our previous study 39 . Dedifferentiation has been observed in various tissues during regeneration; however, subtle differences in the mechanism of dedifferentiation are observed between the taste bud and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of taste organoids, this makes it difficult for mature taste cells to be presented with tastants in in vitro experiments. However, the work published by Adpaikar and colleagues ( 368 ) revealed that transferring organoids grown in the basement membrane, into suspension culture could reverse this apicobasal polarity, thus producing taste organoids with mature TRCs localized on its apical surface. Furthermore, they also observed that attempts to grow single cell-derived mouse taste organoids directly in suspension culture were not successful.…”
Section: Research In Progressmentioning
confidence: 99%
“…Furthermore, they also observed that attempts to grow single cell-derived mouse taste organoids directly in suspension culture were not successful. The mouse taste organoids first cultured in the basement membrane and then in suspension culture showed cell differentiation and renewal rates that are more similar to the native tissue, had TRCs that are more accessible to calcium imaging (thus enabling evaluation of taste transduction), and could subsequently be integrated into the host lingual epithelium without impeding its functional capacity ( 368 ).…”
Section: Research In Progressmentioning
confidence: 99%
“…Adpaikar et al developed a new approach to culturing taste bud organoids by establishing suspension-cultured organoids that maintain the correct polarity of taste buds. This advancement is significant because it enables direct measurement of taste responses, and the high accessibility of taste organs makes them an ideal model for in vitro studies (Adpaikar et al 2022). With further advances in biosensing technology, tongue organoids may develop to have biological functions, providing a platform for taste-related in vitro studies and regenerative therapies.…”
Section: Stem Cell-based Taste Treatmentmentioning
confidence: 99%